Study of Park and Ride Facilities in Cikarang - Annisa Annisa; Leonardus Bambang Budi Prasetyo (JOURNAL OF APPLIED SCIENCE (JAPPS), 2021)
The enormous number of Cawang-Cikarang toll road private vehicles users have caused congestion in Jakarta. To reduce congestion in Jakarta, suburban areas, such as Cikarang, commuters shall utilize Park and Ride (P&R) facilities than use private vehicle to Jakarta. This study is important to give the commuters information of P&R in Cikarang, so they can make an option of their trip. P&R facility has a main function as a hub to change from private vehicle to public transportation. Observation as well as questionnaire were used to reveal findings for this study, the data results are analyzed with descriptive statistics. This study revealed that users of P&R facilities from Cikarang are generally commuters who have offices in urban areas and reside in suburban areas. The problem that occurs in Cikarang is that parking facilities in transit locations (stations / terminals / stops) have not been utilized optimally. This study aims to analyze the actual state and user satisfaction of P&R facility in Cikarang. The six locations include: (1) Cikarang Station; (2) Metland Telaga Murni Station; (3) Lemahabang Station; (4) Cikarang Terminal; (5) Capitol Stop; and (6) AO Citywalk Lippo Cikarang Bus Stop. The results showed that the majority of respondents (N=231) were satisfied (m=3.78; SD=0.99, p